The Mechanism of Corporate Governance, Financial Performance, and Social Performance in Baitul Maal Wat Tamwil (BMT) - Hasan Mukhibad; Ahmad Nurkhin (JASF: Journal of Accounting and Strategic Finance, 2020)
This study aimed to empirically prove the influence of the number and education level of managers, supervisory boards, Sharia Supervisory Board (SSB) and the attendance of Baitul Maal wat Tamwil (BMT) members (owners) in annual member meeting towards on profitability (ROA and ROE), and social performance (zakat performance). The research sample was BMT in Semarang Regency selected by purposive sampling method with an observation period from 2013 to 2017. Data analysis used the Structure Equation Model with the WarpPLS tool. The results showed that the number and education level of managers did not influence financial performance. The education level of the supervisory board had a significant influence on financial and social performance. The number and the education level of SSB changed financial performance, but the education level of SSB did not affect social performance. The Attendance of BMT members at the annual member meeting did not have a significant influence on BMT's financial and social performance improvement. These results indicated the minimal role of members in evaluating BMT performance, both profitability and social performance.